2010
DOI: 10.1016/j.molcel.2010.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Translational Regulation of Gene Expression during Conditions of Cell Stress

Abstract: A number of stresses, including nutrient stress, temperature shock, DNA damage, and hypoxia, can lead to changes in gene expression patterns caused by a general shutdown and reprogramming of protein synthesis. Each of these stress conditions results in selective recruitment of ribosomes to mRNAs whose protein products are required for responding to stress. This recruitment is regulated by elements within the 5' and 3' untranslated regions of mRNAs, including internal ribosome entry segments, upstream open read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
596
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 640 publications
(614 citation statements)
references
References 110 publications
17
596
0
1
Order By: Relevance
“…1b). In contrast, ATF4 mRNA (which escapes eIF2a-P-mediated inhibition of translation, owing to the presence of upstream open reading frames in its 59 untranslated region (UTR) 17,18 ), showed increased active translation, represented by a right shift to a higher polysomal fraction ( Fig. 2j and Supplementary Figs 4 and 5).…”
Section: Research Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…1b). In contrast, ATF4 mRNA (which escapes eIF2a-P-mediated inhibition of translation, owing to the presence of upstream open reading frames in its 59 untranslated region (UTR) 17,18 ), showed increased active translation, represented by a right shift to a higher polysomal fraction ( Fig. 2j and Supplementary Figs 4 and 5).…”
Section: Research Lettermentioning
confidence: 99%
“…PrP mRNA did not show reduced translation, possibly because of the existence of similar translational control elements within the PrP gene. Indeed, human PrP mRNA has multiple upstream AUG upstream open reading frames in its 59 UTR, which could allow it to escape eIF2a-P translational inhibition in the same way as ATF4 does 17,18 ( Supplementary Fig. 6).…”
Section: Research Lettermentioning
confidence: 99%
“…In this study, we showed that FXR is a novel target of miR-421 in HCC cells, and downregulation of FXR may be a new oncogenic mechanism of miR-421. miRNAs can target mRNAs at the 3 0 -UTR/5 0 -UTR, even at the open reading frame (ORF) by partial sequence homology, leading to translation repression/mRNA degradation (20)(21)(22). The current miRNA databases, such as miRBase, TargetScan, miRanda, and so on, are usually used for predicting the miRNAs for a target gene or predicting the targets of a miRNA based on the 3 0 -UTR sequences of mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Hypoxic culture conditions for MCF7 cells transfected with pRuF plasmids caused a significant increase in Fluc activity for the plasmids harboring either c-MYC or PTCH1b 5'UTR, but not when the putative PTCH1b IRES motif was deleted (Fig. 6, left panel).…”
Section: Hypoxia Can Stimulate Ptch1b 5'utr-mediated Cap-independentmentioning
confidence: 97%